Trans black women deserve better: expanding queer criminology to unpack trans misogynoir in the field of criminology - Mikell, Toniqua (Abolish criminology, 2022)
The criminalization of Blackness and queerness, coupled with the misogynoir entrenched in the fabric of a white hetero-patriarchal society, positions trans Black women in the center of a very dangerous matrix of domination amid interlocking systems of oppression. Currently, the ‘queering’ of criminology study and practice alienates queer liberation leaders and people most at risk for criminalization and victimization – trans Black women. Using an intersectional abolitionist lens, this chapter challenges existing queer criminology paradigms arguing that white cisgender gay men have monopolized the public understanding of queer people, leading to research and policy that further marginalizes the most vulnerable communities. This chapter concludes with a discussion on the necessity of intersectional queer criminological abolitionist approaches to understand the risk factors for criminal legal system entanglement and outcomes for Black trans women.